THE ROLE AND SIGNIFICANCE OF PHARMACOECONOMIC ANALYSIS IN THE HEALTHCARE SYSTEM (literature review) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Pharmacoeconomic analysis is a method for assessing the rationality of the use of financial and pharmaceutical products in the healthcare system. It allows you to determine the most optimal options for using medications based on data on their cost and effectiveness. This articleexamines the role of pharmacoeconomic analysis in the health care system and its implications fordecision-making on the best treatment strategies. It also emphasizes the importance of conductingsuch analysis as a means of improving the quality and accessibility of medical care, reducing treatment costs and increasing the economic efficiency of the health care system as a whole.
Keywords: pharmacoeconomics, healthcare system, medicines, effectiveness, costs.